Fighting Flu in Asia: Comparative Study of Response Policies in Yogyakarta, Indonesia and Daegu, South Korea - Setiawati, Nur Aini; Wasino, Wasino; Pratama, Safrial Fachry; Horton, William Bradley; Sina, Fortuna Devi Putri (Paramita: Historical Studies Journal, 2024)
The history of influenza outbreaks extends back to the colonial era. Notably, the 1918 pandemic, often referred to as the Spanish flu, is estimated to have claimed the lives of approximately 100 million people worldwide. In historical development, influenza outbreaks reappeared from 1957 to 2022 in Yogyakarta, Indonesia, Daegu, South Korea, and even the world. This study uses historical research methods to examine policies for handling influenza so people can take preventive measures to prevent it. The Korean and Indonesian sources used include the collections of Gouvernement Besluit, Staatsblad, Bijblad, Rijksblad, and contemporary newspapers and the Korean Archives will be accessed through the Korean government’s official website, namely, Guksaphyeonchanwiwonhwe (National Institute of Korea) as well as the Royal Notes archive: Collection of Joseon Wangjo Sillok, accompanied by primary sources through FGDs and interviews. This paper proves there has been a delay in the response from the Indonesian government to deal with influenza, in contrast to the South Korean government, which is quicker and more responsive in suppressing the bad implications of influenza.Sejarah wabah influenza dimulai pada era kolonial. Khususnya, pandemi tahun 1918, yang sering disebut sebagai flu Spanyol, diperkirakan telah merenggut nyawa sekitar 100 juta orang di seluruh dunia. Dalam perkembanganya, wabah influenza muncul kembali pada tahun 1957 hingga 2022 di Yogyakarta, Indonesia, Daegu, Korea Selatan, bahkan dunia. Penelitian ini menggunakan metode penelitian sejarah untuk mengkaji kebijakan penanganan influenza sehingga masyarakat dapat melakukan tindakan preventif untuk mencegahnya. Sumber Korea dan Indonesia yang digunakan antara lain koleksi Gouvernement Besluit, Staatsblad, Bijblad, Rijksblad, dan surat kabar kontemporer serta Arsip Korea akan diakses melalui situs resmi pemerintah Korea yaitu Guksaphyeonchanwiwonhwe (National Institute of Korea) serta Royal Arsip: Kumpulan Catatan Joseon Wangjo Sillok disertai narasumber primer melalui FGD dan wawancara. Tulisan ini membuktikan adanya keterlambatan respon pemerintah Indonesia dalam menangani influenza, berbeda dengan pemerintah Korea Selatan yang lebih cepat dan tanggap dalam menekan dampak buruk influenza.